ANALISIS PERAN GURU SOSIOLOGI DALAM PENGENDALIAN KONFLIK ANTAR SISWA DI KELAS - Dari, Dina Wulan; Imran, Imran; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The general problem of this research is the Role of Sociology Teachers in Conflict Control Between Students in Class XI IIS 3 Madrasah Aliyah Negeri Singkawang City. The research method used is a qualitative research method with a descriptive research type. The results of thisstudy which are (1) Conflict control between students by means of prevention by the sociology teacher has been going well, this is proven by sociology teachers always giving advice, guiding and giving direction and invitations to students, who are involved in conflict when interruptedlearning process and end of learning. (2) Conflict control between students in a repressive way carried out by the sociology teacher has been going well, this is evidenced by the teacher of sociology has given punishment to students who are in conflict and gave a reprimand to otherstudents so as to mediate and prevent conflict. (3) Conflict control between students by means of curative conducted by the sociology teacher of two conflicting students has been going well whichcan be seen from the sociology teacher who asked students to write a statement letter not to repeat and there was a calling to the student’s parens.Keywords: Conflict Control, MAN, Students, Teachers